Long-term trends in dietary intake of perfluoroalkyl carboxylic acids in relation to their serum concentration in two regions in Japan from 1979 to 2011. (June 2017) - Fujii, Yukiko; Harada, Kouji H.; Haraguchi, Koichi; Koizumi, Akio
Abstract: We investigated temporal changes of perfluoroalkyl carboxylic acids (PFCAs) with 8–14 carbon atoms (C8 to C14) in duplicate diet and serum samples in Japan. The sum dietary intakes of PFCAs (C8 to C13) in the Kansai and Tohoku region were highest in the 2010s (mean; 177 ng/day for Kansai, 107 ng/day for Tohoku) followed by the 2000s (77 ng/day for Kansai, 34 ng/day for Tohoku) and the 1990s (53 ng/day for Kansai, 58 ng/day for Tohoku), then the 1980s (19 ng/day for Kansai, 23 ng/day for Tohoku). The sum of the serum concentartions (C8 to C13) was also highest in the 2010s (mean; 17 ng/mL for Kansai, 7.4 ng/mL for Tohoku), followed by the 2000s (12 ng/mL for Kansai, 6.3 ng/mL for Tohoku), then the 1990s (6.8 ng/mL for Kansai, 5.5 mg/mL for Tohoku) and the 1980s (3.8 ng/mL for Kansai, 0.4 ng/mL for Tohoku). A positive correlation was observed between dietary intakes and serum concentration for C8 to C11 (r = 0.94, p < 0.05 for C8; r = 0.80, p < 0.05 for C9; r = 0.98, p < 0.05 for C10; and r = 0.84, p < 0.05 for C11). The levels of C8, C9 and C10 in serum and dietary intake in the 2010s were much higher in Kansai than those in Tohoku, although those of C11 did not show such differences. Kansai has a fluoropolymer manufacture known as a specific source of PFOA (C8), and is more urbanized than Tohoku, which may be attributed to the higher levels of PFCAs (C8 to C10). On the other hand, C11 is common to residents in Kansai and Tohoku. Highlights: Perfluoroalkyl carboxylic acids (PFCAs) in diet and serum have been investigated. The analyzed samples obtained since the 1980s until the 2010s. A positive correlation was observed between diet and serum concentration of PFCAs. This indicates that dietary intake may be a source of C8–C11 PFCAs exposure.